2021
DOI: 10.1158/1940-6207.capr-20-0123
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aspirin, Metformin, and Statin Use with Gastric Cancer Incidence and Mortality: A Nationwide Cohort Study

Abstract: Anticancer effects of aspirin, metformin, and statins against gastric cancer, one of the most common cancers in the world, have been reported. This retrospective cohort study aimed to investigate independent associations of aspirin, metformin, and statin use with gastric cancer incidence and mortality after adjustment for concomitant use of other drugs, using pooled cohort data extracted from the Korean National Health Insurance claim database. Follow-up started on January 1, 2004 and ended at the date of gast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…However, the results of a population-based epidemiologic study showed that the use of statins was not associated with overall prostate cancer risk [67], although the credibility of the results of the study are open to question due to the relatively small sample size and the existence of potential selection and recall biases. In gastric cancer, a recent nationwide cohort study suggested that the use of statins is related to a decrease in gastric cancer mortality in the general population, but has no correlation with the incidence of gastric cancer [30]. A recent prospective observational study of ovarian cancer patients conducted in Australia suggested that the increase in patient survival is related to the use of lipophilic statins, but not to hydrophilic statins [59].…”
Section: Population-based Studiesmentioning
confidence: 99%
“…However, the results of a population-based epidemiologic study showed that the use of statins was not associated with overall prostate cancer risk [67], although the credibility of the results of the study are open to question due to the relatively small sample size and the existence of potential selection and recall biases. In gastric cancer, a recent nationwide cohort study suggested that the use of statins is related to a decrease in gastric cancer mortality in the general population, but has no correlation with the incidence of gastric cancer [30]. A recent prospective observational study of ovarian cancer patients conducted in Australia suggested that the increase in patient survival is related to the use of lipophilic statins, but not to hydrophilic statins [59].…”
Section: Population-based Studiesmentioning
confidence: 99%
“…Other commonly prescribed medications have been proposed as possibly chemopreventive for gastric cancer development, including statins, NSAIDs, metformin, and COX-2 inhibitors [ 11 14 ]. However, existing studies have not yet specifically examined the potential protective role of these medications in EOGC.…”
Section: Discussionmentioning
confidence: 99%
“…Other frequently prescribed medications, including statins (HMG-CoA reductase inhibitors), metformin, nonsteroidal anti-inflammatory medications (NSAIDs), and cyclooxygenase-2 (COX-2) inhibitors, have also been associated with a potentially reduced risk of gastric cancer development [ 11 13 ]. Statin medications have been proposed to have antiangiogenic, immunomodulatory, and proapoptotic properties based on in vitro studies in mice and human gastric cancer cell lines, as well as in retrospective studies [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between statin use and lower GC risk remains elusive, and some discrepancies have emerged. A study by Cho et al showed that statins were able to reduce mortality in GC but failed to decrease its incidence [ 98 ]. These findings are inconsistent with results from previous systematic reviews and meta-analyses, which may be because different study populations and settings were analyzed [ 17 ].…”
Section: Statin Use Reduces Gc Riskmentioning
confidence: 99%